Green and Facile Synthesis of Spirocyclopentanes Through NaOH-Promoted Chemo- and Diastereo-Selective (3 + 2) Cycloaddition Reactions of Activated Cyclopropanes and Enamides - Zhu, Xun; Pan, Dingwu; Mou, Chengli; Zhou, Bo; Pan, Lutai; Jin, Zhichao (Frontiers in Chemistry, 2020)
A chemo-and diastereo-selective [3 + 2] cycloaddition reacition between Donor-Acceptor (D-A) cyclopropanes and α,β-unsaturated enamides is developed for efficient access to spiro[cyclopentane-1,3'-indoline] derivatives. Simple, inexpensive and readily available NaOH is used as the sole catalyst for this process. A broad range of D-A cyclopropanes could be used as the C-3 synthons to react with oxindole-derived α,β-unsaturated enamides. The structurally sophisticated spiro[cyclopentane-1,3'-indoline] derivatives bearing up to 3 adjacent chiral centres are afforded in excellent yields as single diastereomers.